Neuroimaging Finding of Organic Academia in Children - KHATAMI, Alireza (Iranian Journal of Child Neurology, 2012)
Organic academia are diverse group of disorders characterized by abnormal degredation of specific amino acid in the specific catabolism due to an enzymeactivity defect which mainly due to enzyme deficiency. The majority of the classic organic acid disorders are caused by abnormal catabolism of branched-chain amino acids like lysine. maple syrup urine disease (MSUD), propionic acidemia, methylmalonic acidemia (MMA), Ethylmalonic academia,glutaricacidemia type I and so on. The most common presentation is related to toxic encephalopathy which are as follows: vomiting, poor feeding,neurologic symptoms such as seizures and abnormal tone, and lethargy progressing to coma and the outcome may be loss of intellectual function, ataxia, psychiatric symptoms and other neurological deficit.Along with laboratory tests, Imaging have some characteristic findings in determination of these wide range of disease and can help in categorization and differentiation these form of brain metabolic disorders in conjunction by other investigative study. In this lecture trying to review imaging findings of more common organic academia in children will be done.